2008
DOI: 10.1016/j.ijgo.2008.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and traditional postpartum care in China: Role of Zuoyuezi

Abstract: These data highlight the importance of the peripartum experience in assessing PPD risk. Zuoyuezi is still commonly practiced in urban China, and further research is needed to explore its role in the potential prevention of PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 22 publications
5
75
3
Order By: Relevance
“…Such difficulties included having a partner who rejected paternity, who was unsupportive and uninvolved, or critical and quarrelsome, and who used alcohol to excess. 8,27,28,31,38,39,45,48 Higher average symptom scores among women in polygamous rather than monogamous marriages were found in Nigeria 53 and Nepal, 31 but not in Ethiopia. 30 Only seven 24,25,28,[30][31][32]40 studies investigated an association with intimate partner violence.…”
Section: Quality Of Relationship With Intimate Partnermentioning
confidence: 90%
See 4 more Smart Citations
“…Such difficulties included having a partner who rejected paternity, who was unsupportive and uninvolved, or critical and quarrelsome, and who used alcohol to excess. 8,27,28,31,38,39,45,48 Higher average symptom scores among women in polygamous rather than monogamous marriages were found in Nigeria 53 and Nepal, 31 but not in Ethiopia. 30 Only seven 24,25,28,[30][31][32]40 studies investigated an association with intimate partner violence.…”
Section: Quality Of Relationship With Intimate Partnermentioning
confidence: 90%
“…Rates of CPMD were also higher among women who were young 9,37,49 ; of a religious minority, 34 or unmarried. 13,39,55 However, other studies found no association between CPMD and maternal age 10,13,16,20,22,32,36,45,48 ; marital status 9,34,37,47 ; economic difficulties or a low income 13,22,26,32,36,45,48 ; unemployment 9,16,26,34,36,47 or adverse life events. 10,31…”
Section: Systematic Reviewsmentioning
confidence: 92%
See 3 more Smart Citations